In vitro anti-inflammatory, anti-arthritic and anti- proliferative activity of green synthesized silver nanoparticles - Phoenix dactylifera (Rothan dates) - Syed Zameer Ahmed Khader; Sidhra Syed Zameer Ahmed; Mohamed Rafi Mahboob; Selva Barathi Prabaharan; Shanmugasundaram Olapalayam Lakshmanan; Kishore Ramesh Kumar; Daniel David (Universidade de São Paulo, 2022)
Abstract Traditionally dates is consumed as a rich source of iron supplement and the current research discuss the synthesis of silver nanoparticles (AgNPs) using methanolic seed extract of Rothan date and its application over in vitro anti-arthritic, anti-inflammatory and antiproliferative activity against lung cancer cell line (A549). FTIR result of synthesised AgNPs reveals the presence of functional group OH as capping agent. XRD pattern confirms the crystalline nature of the AgNPs with peaks at 38º, 44º, 64º and 81º, indexed by (111), (200), (220) and (222) in the 2θ range of 10-90, indicating the face centered cubic (fcc) structure of metallic Ag. HR- TEM results confirm the morphology of AgNPs as almost spherical with high surface areas and average size of 42 ± 9nm. EDX spectra confirmed that Ag is only the major element present and the Dynamic light scattering (DLS) assisted that the Z-average size was 203nm and 1.0 of PdI value. Zeta potential showed − 26.5mv with a single peak. The results of the biological activities of AgNPs exhibited dose dependent activity with 68.44% for arthritic, antiinflammatory with 63.32% inhibition and anti-proliferative activity illustrated IC50 value of 59.66 μg/mL expressing the potential of AgNPs to combat cancer.